Evaluation of SARS Cov-2 disease epidemiology, clinical and diagnostic profile-a regional study from tertiary care center of North India - Arti Agrawal,; Astha,; Vikas Kumar,; Dharmendra Kumar,; Neelika Tripathi,; Sanjeev Kumar, (Asian Journal of Medical Sciences, 2024)
Background: A novel coronavirus severe acute respiratory syndrome coronavirus-2 (SARSCoV-2) that emerged in China in December 2019 has spread rapidly globally to many countries including India and World Health Organization declared it as a pandemic on March 11th, 2020. Aims and Objectives: The current study endeavors to determine the SARS-CoV-2 positivity rate as well as epidemiological, clinical, and diagnostic profiles from the second wave. Materials and Methods: We performed a retrospective analysis of all suspected COVID-19 cases from January 2021 to October 2021 presenting at a large testing center for SARS-CoV-2 infection by real-time polymerase chain reaction (RT-PCR). Descriptive analysis has been performed for profiling of clinical-epidemiological aspects of suspected cases. Results: A total of 694427 participants were enrolled during the study from January 2021 to October 2021. Overall RT-PCR positivity rate was found to be 1.7% in the year 2021 and the positivity was maximum in April 2021 which represents the second wave of COVID-19 infection in India. In the study population, more than half (57.07%) of the persons screened for COVID-19 infection were between 21 and 40 years of age, and about two-thirds (65.20%) of the persons screened were male followed by 34.79% were female. Conclusions: SARS-CoV-2 poses a high burden of infections in the community. Males had a higher RT-PCR detection rate as compared to females. The younger age group (<20 years) expressed the least RT-PCR positivity rate and the elderly population (>80 years) expressed the highest positivity rate.